Cat Kid comic club. Collaborations - Pilkey, Dav, 1966- (Graphix, 2022)
The members of the Cat Kid Comic Club learn all about the power of collaboration as they continue to make comics together. The baby frogs soon discover that even the smallest things can have a huge impact.